2017
DOI: 10.1371/journal.pone.0174990
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal MCT2 knockdown in the rat somatosensory cortex reduces both the NMR lactate signal and the BOLD response during whisker stimulation

Abstract: Although several in vitro and ex vivo evidence support the existence of lactate exchange between astrocytes and neurons, a direct demonstration in vivo is still lacking. In the present study, a lentiviral vector carrying a short hairpin RNA (shRNA) was used to downregulate the expression of the monocarboxylate transporter type 2 (MCT2) in neurons of the rat somatosensory cortex (called S1BF) by ~ 25%. After one hour of whisker stimulation, HRMAS 1H-NMR spectroscopy analysis of S1BF perchloric acid extracts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(91 citation statements)
references
References 55 publications
5
85
1
Order By: Relevance
“…These results (and others in Díaz‐García et al, ) argue strongly that neuronal NADH CYT signals are produced not by import of astrocytic lactate, but rather by stimulation of neuronal aerobic glycolysis, both in stimulated dentate granule neurons of the hippocampus and in L2/3 neurons of somatosensory barrel cortex (activated by whisker stimulation). Further, these results are consistent with the experimental results of Mazuel et al () measuring lactate increases in stimulated barrel cortex, with or without knockdown of neuronal MCT2. These experiments showed that prolonged stimulation increased the lactate content of barrel cortex, but that this effect was absent when neuronal MCT2 was knocked down.…”
Section: Changes Of Nadhcyt Upon Neuronal Stimulation Results From Glysupporting
confidence: 92%
See 2 more Smart Citations
“…These results (and others in Díaz‐García et al, ) argue strongly that neuronal NADH CYT signals are produced not by import of astrocytic lactate, but rather by stimulation of neuronal aerobic glycolysis, both in stimulated dentate granule neurons of the hippocampus and in L2/3 neurons of somatosensory barrel cortex (activated by whisker stimulation). Further, these results are consistent with the experimental results of Mazuel et al () measuring lactate increases in stimulated barrel cortex, with or without knockdown of neuronal MCT2. These experiments showed that prolonged stimulation increased the lactate content of barrel cortex, but that this effect was absent when neuronal MCT2 was knocked down.…”
Section: Changes Of Nadhcyt Upon Neuronal Stimulation Results From Glysupporting
confidence: 92%
“…These experiments showed that prolonged 5 Barros and Weber (2018) have remarked on the fact that the lactate transient was not increased with MCT inhibition, and taken this as evidence that neurons do not contribute to the accumulation of lactate. However, the reduced dips in glucose with MCT inhibition indicate that the increased NADH CYT exerted back-pressure on glycolysis (as discussed below; this is also the implication of the Mazuel et al (2017) study discussed below). In addition, the signal-to-noise ratio for the lactate determination is smaller than for NADH CYT , and lactate is a less sensitive measure than NADH CYT .…”
Section: Similarly Biosensor Monitoring Of the Intracellular [Lactatmentioning
confidence: 91%
See 1 more Smart Citation
“…; Mazuel et al . ). Significantly, the deletion of MCTs in glial cells but not in neurons could be rescued by lactate, meaning that maintaining function requires neurons to have access to extracellular lactate.…”
Section: Experiments In Cultured Cellsmentioning
confidence: 97%
“…Irrespective of accumulating evidence supporting the ANLSH, the fate of lactate, if it is really produced by astroglia via a glutamate signal from activated neurons, has remained a matter of controversy for more than 25 years . The original ANLSH followed by numerous reports proposed that activated neurons consume lactate produced by astroglia . A strong argument for this is based on a kinetic property of MCT2 expressed in neurons, which has a low kilometer value.…”
Section: Glucose and Lacatementioning
confidence: 99%